Asymmetric Landau bands due to spin–orbit coupling. (18th May 2015) - Erlingsson, Sigurdur I; Manolescu, Andrei; Marinescu, D C
Abstract: We show that the Landau bands obtained in a two-dimensional lateral semiconductor superlattice with spin–orbit coupling (SOC) of the Rashba/Dresselhaus type, linear in the electron momentum, placed in a tilted magnetic field, do not follow the symmetry of the spatial modulation. Moreover, this phenomenology is found to depend on the relative tilt of magnetic field and on the SOC type: (a) when only Rashba SOC exists and the magnetic field is tilted in the direction of the superlattice (b) Dresselhaus SOC exists and the magnetic field is tilted in the direction perpendicular to the superlattice. Consequently, measurable properties of the modulated system become anisotropic in a tilted magnetic field when the field is conically rotated around the z axis, at a fixed polar angle, as we demonstrate by calculating the resistivity and the magnetization.